PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE LISTENING TEAM UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VA SD NEGERI 158 PEKANBARU - Yeny Oriz Samosir; Hendri Marhadi; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This research is based on a problem found in the A 5th grade class of SDN 158 Pekanbaru, that is the low learning result of social majored students. It can be seen on the students score reaching KKM (Minimal Criteria) which is only 6 people (25%) from 24 students . While the school established KKM is at 70, then many students who have not reached the KKM is 18 students (75%). Based on these problems it is necessary to apply cooperative learning model type Listening Team in order to help improving student learning outcomes. Cooperative learning model type Listening Team begins with the exposure of subject matter, then teachers divide students into four groups with different roles and tasks (questions asker, answers giver, rebutter,conclusion maker). If active learning is active, it is expected to affect student learning outcomes. The purpose of this study is to improve learning outcomes social majored students A 5thgrade class of SD Negeri 158 Pekanbaru. This research was conducted in 2 cycles. The data collected in this research is the data of Teacher and Student activity and test data of student learning result on daily test in every cycle. In the first cycle of teacher activity increased by 70.83% (enough) and 75.00% (enough) then in the second cycle reached by 87.50% (very good) and 95.83% (very good). It also happens on student activity with the percentage gain in the first cycle by 66,67% (enough) and 70,83% (enough) then at the second cycleby 83,33% (very good) and 91,67% (very good). In addition to teacher and student activity, social students learning outcomes also experienced an increase from the average basic score of 59.37 with a 25% completeness percentage increase in the first cycle of 18.94% to 70.62 with a percentage of 62.50% completeness. Then at second cycle increased again by 4.58% to 75.20 with the percentage mask 87.50%. So it can be concluded that cooperative learning model type listening team can improve learning result of social majored students A 5thgrade class of SD Negeri 158 Pekanbaru.Keywords: Listening Team, Learning Results IPS